Increased disease activity, severity and autoantibody positivity in rheumatoid arthritis patients with co‐existent bronchiectasis. (22nd July 2015) - Perry, Elizabeth; Eggleton, Paul; De Soyza, Anthony; Hutchinson, David; Kelly, Clive
Abstract: Aim: Patients with rheumatoid arthritis (RA) and co‐existent bronchiectasis (BRRA) have a five‐fold increased mortality compared to rheumatoid arthritis alone. Yet previous studies have found no difference in clinical and serological markers of RA disease severity between BRRA patients and RA alone. However, RA disease activity measures such as Disease Activity Score of 28 joints – C‐reactive protein (DAS28‐CRP) and anti‐cyclic citrullinated peptide antibodies (anti‐CCP) have not been studied, so we assessed these parameters in patients with BRRA and RA alone. Methods: BRRA patients ( n = 53) had high‐resolution computed tomography proven bronchiectasis without any interstitial lung disease and ≥ 2 respiratory infections/year. RA alone patients ( n = 50) had no clinical or radiological evidence of lung disease. DAS28‐CRP, rheumatoid factor (immunoglobulin M) and anti‐CCP were measured in all patients, together with detailed clinical and radiology records. Results: In BRRA, bronchiectasis predated RA in 58% of patients. BRRA patients had higher DAS28 scores (3.51 vs . 2.59), higher levels of anti‐CCP (89% vs . 46%) and rheumatoid factor (79% vs . 52%) ( P = 0.003) compared to RA alone. Where hand and foot radiology findings were recorded, 29/37 BRRA (78%) and 13/30 (43%) RA alone had evidence of erosive change ( P = 0.003). There were no significant differences between groups in smoking history or disease‐modifying anti‐rheumatic drug/biologic therapy. Conclusions: Increased levels of RA disease activity, severity and RA autoantibodies are demonstrated in patients with RA and co‐existent bronchiectasis compared to patients with RA alone, despite lower tobacco exposure. This study demonstrates that BRRA is a more severe systemic disease than RA alone.